LIFE AND WORK OF MIKHAIL IVANOVICH GLINKA (Conferencea, 2022)
This article provides full information about the life of the great composer Mikhail Ivanovich Glinka, one of the founders of Russian classical music, the similarities and differences between the works created by Glinka and the works created by other composers, and how the works illuminate different aspects and aspects of the life of the Russian people.